Digital control of electrical drives - Vukosavic, Slobodan N. ([S.l.] : Springer, 2007)
Provides broad insights into problems of coding control algorithms on a DSP platform. - Includes a set of Simulink simulation files (source codes) which permits readers to envisage the effects of control solutions on the overall motion control system. -bridges the gap between control analysis and industrial practice.